Persepsi Konsumen Produk Teri Crispy Kampung Nelayan Maju di Kota Samarinda - Ayuni Ayang Kumara; Fitriyana Fitriyana; Etik Sulistowati Ningsih (Lembaga Pengembangan Kinerja Dosen, 2023)
This research was conducted with the aim of understanding Consumer Perception of Crispy Anchovy Products from the Fishing Village of Maju Rawa Makmur, Palaran Subdistrict, Samarinda City. The research was carried out in the Fishing Village of Maju Rawa Makmur, Palaran Subdistrict, Samarinda City. The sampling methods used were purposive sampling and accidental sampling with 25 consumers. The data analysis method used was qualitative analysis, which is structured, focused, and specific, yet flexible and subject to change as needed.Based on the research findings, it was found that concerning the taste of crispy anchovies, the majority of consumers (80%) rated it as